Ba(BO2OH) – A Monoprotonated Monoborate from Hydroflux Showing Intense Second Harmonic Generation - Li, Yuxi; Hegarty, Peter A.; Rüsing, Michael; Eng, Lukas M.; Ruck, Michael (Zeitschrift für anorganische und allgemeine Chemie)
Abstract Pure samples of colorless, air‐stable Ba(BO 2 OH) crystals were obtained from Ba(NO 3 ) 2 and H 3 BO 3 under the ultra‐alkaline conditions of a KOH hydroflux at about 250 °C. The product formation depends on the water‐base molar ratio and the molar ratio of the starting materials. B(OH) 3 acts as a proton donor (Brønsted acid) rather than a hydroxide acceptor (Lewis acid). Ba(BO 2 OH) crystallizes in the non‐centrosymmetric orthorhombic space group P 2 1 2 1 2 1 . Hydrogen bonds connect the almost planar (BO 2 OH) 2− anions, which are isostructural to HCO 3 − , into a syndiotactic chain. IR and Raman spectroscopy confirm the presence of hydroxide groups, which are involved in weak hydrogen bonds. Upon heating in air to about 450 °C, Ba(BO 2 OH) dehydrates to Ba 2 B 2 O 5 . Moreover, the non‐centrosymmetric structure of Ba(BO 2 OH) crystals was verified with power‐dependent confocal Second Harmonic Generation (SHG) microscopy indicating large conversion efficiencies in ambient atmosphere.
Keywords: Inorganic Chemistry

On the Existence of LiFeVO4 - Tales and Imagination - Clemens, Oliver; Bauer, Matthias; Haberkorn, Robert; Beck, Horst Philipp (Zeitschrift für anorganische und allgemeine Chemie)
Keywords: Inorganic Chemistry

Systematische Studie zu den Koordinationseigenschaften des Guanidin‐Liganden Bis(tetramethylguanidino)propan mit den Metallen Mangan, Cobalt, Nickel, Zink, Cadmium, Quecksilber und Silber - Neuba, Adam; Herres‐Pawlis, Sonja; Seewald, Oliver; Börner, Janna; Heuwing, Andreas J.; Flörke, Ulrich; Henkel, Gerald (Zeitschrift für anorganische und allgemeine Chemie)
Abstract The transition metal complexes with the ligand 1,3‐bis( N , N , N′ , N′ ‐tetramethylguanidino)propane (btmgp), [Mn(btmgp)Br 2 ] ( 1 ), [Co(btmgp)Cl 2 ] ( 2 ), [Ni(btmgp)I 2 ] ( 3 ), [Zn(btmgp)Cl 2 ] ( 4 ), [Zn(btmgp)(O 2 CCH 3 ) 2 ] ( 5 ), [Cd(btmgp)Cl 2 ] ( 6 ), [Hg(btmgp)Cl 2 ] ( 7 ) and [Ag 2 (btmgp) 2 ][ClO 4 ] 2 ·2MeCN ( 8 ), were prepared and characterised for the first time. The stoichiometric reaction of the corresponding water‐free metal salts with the ligand btmgp in dry MeCN or THF resulted in the straightforward formation of the mononuclear complexes 1 – 7 and the binuclear complex 8 . In complexes with M II the metal ion shows a distorted tetrahedral coordination whereas in 8 , the coordination of the M I ion is almost linear. The coordination behavior of btmgp and resulting structural parameters of the corresponding complexes were discussed in an comparative approach together with already described complexes of btmgp and the bisguanidine ligand N 1 ,N 2 ‐bis(1,3‐dimethylimidazolidin‐2‐ylidene)‐ethane‐1,2‐diamine (DMEG 2 e), respectively.

Synthese und Struktur chiraler Heterometallatetrahedrane des Typs [Re2(M1PPh3)(M2PPh3)(μ‐PCy2)(CO)7C≡CPh] (M1 = Ag, Au; M2 = Cu, Ag, Au) - Seewald, Oliver; Flörke, Ulrich; Egold, Hans; Haupt, Hans‐Jürgen; Schwefer, Meinhard (Zeitschrift für anorganische und allgemeine Chemie)
Abstract Syntheses and Structure of Chiral Metallatetrahedron Complexes of the Type [Re 2 (M 1 PPh 3 )(M 2 PPh 3 )(μ‐PCy 2 )(CO) 7 C≡CPh] (M 1 = Ag, Au; M 2 = Cu, Ag, Au) From the reaction of Li[Re 2 (μ‐H)(μ‐PCy 2 )(CO) 7 (C(Ph)O)] ( 1 ) with Ph 3 AuC≡CPh both benzaldehyde and the trinuclear complex Li[Re 2 (AuPPh 3 )(μ‐PCy 2 )(CO) 7 C≡CPh] ( 2a ) were obtained in high yield. The complex anion was isolated as its PPh 4 ‐salt 2b . The latter reacts with coinage metal complexes PPh 3 M 2 Cl [M 2 = Cu, Ag, Au] to give chiral heterometallatetrahedranes of the general formula [Re 2 (AuPPh 3 )(M 2 PPh 3 )(μ‐PCy 2 )(CO) 7 C≡CPh] (M 2 = Cu 3a , Ag 3b , Au 3c ). The corresponding complex [Re 2 (AgPPh 3 ) 2 (μ‐PCy 2 )(CO) 7 C≡CPh] ( 3d ) is obtained from the reaction of [Re 2 (AgPPh 3 ) 2 (μ‐PCy 2 )(CO) 7 Cl] ( 4 ) with LiC≡CPh. 3d undergoes a metathesis reaction in the presence of PPh 3 CuCl giving [Re 2 (AgPPh 3 )(CuPPh 3 )(μ‐PCy 2 )(CO) 7 C≡CPh] ( 3e ) and PPh 3 AgCl. Analogous metathesis reactions are observed when 3c is reacted with PPh 3 AgCl or PPh 3 CuCl giving 3a or 3b , respectively. The reaction of 1 with PPh 3 AuCl gives benzaldehyde and Li[Re 2 (AuPPh 3 )(μ‐PCy 2 )(CO) 7 Cl] ( 5a ) which upon reaction with PhLi forms the trinuclear complex Li[Re 2 (AuPPh 3 )(μ‐PCy 2 )(CO) 7 Ph] ( 6a ). Again this complex was isolated as its PPh 4 ‐salt 6b . In contrast to 2b , 6b reacts with one equivalent of Ph 3 PAuCl by transmetalation to give Ph 3 PAuPh and PPh 4 [Re 2 (AuPPh 3 )(μ‐PCy 2 )(CO) 7 Cl] ( 5b ). The X‐ray structures of the compounds 3a , 3b , 3e and 4 are reported.